(3GdceHjhJQs (3dZI hCOGA HGSjc (BBasic /s - (3WGjd, eXgQs ([(3HjQhJ(B] :s (3OGQ GdQGJH GdLGeYjI,s)
(3Jchjf GdceHjhJQ(B.s
Keywords: (3eGjcQhShaJ ajLhGd HjSc (B((3eda MGShH(B)s; (3HjSc (B((3dZI HQeLI(B)s; (3GdMGSHGJ GdEdcJQhfjIs -- (3dZGJs; (3GdHQeLI (B((3MGSHGJ EdcJQhfjI(B)s